Khaos Company : A Commander's Account and Lessons Learned from the 2019 MAGTF Warfighting Exercise - Hanks, Matthew S., 1989- (Book collections on Project MUSE., 2021)
"Khaos Company offers a short story written with the intent to provide Marines with the perspective of what it is like to operate and fight at the company- and small-unit levels in operations of such large scale and scope. This is a story about how a small yet cohesive company of Marines experienced chaos, friction, uncertainty, surprise, failure, success, relationships, and executed the maneuver warfare principles outlined in our doctrinal warfighting philosophy"--